Special Purpose Vehicles and Insolvency Reforms in the Philippines - Gloria O. Pasadilla (Philippine Institute for Development Studies (PIDS), 2005)
This paper focuses on the legal environment, particularly the insolvency system, that would influence the success of Philippine Special Purpose Vehicles (SPVs), also known as asset management companies (AMCs) in other countries. Since SPVs will have to operate under a given insolvency regime after they acquire the bad assets, existing bankruptcy procedures have an impact on SPV behavior, ex-ante. In particular, it influences the price that SPVs offer for the NPAs that, in turn, affects the banks willingness to sell, and thus the achievement of the government goal of banks bad loans clean-up. The paper discusses the features of the SPV Act, the pace of bad asset transfers to SPVs, the current rehabilitation procedures, and the proposed legal bankruptcy reforms that would affect the effectiveness of SPVs.
Keywords: 330; banking reforms; asset management company (AMC); bankruptcy; insolvency; nonperforming loans (NPLs); Insolvenz; Insolvenz; Bankenreform; Portfolio-Management; Philippinen